Security and Terrorism Vs Free Expression: Analytical Study on The European Court of Human Rights - Massoud, Mariam Adel (AUC Knowledge Fountain, 2025)
The 11 of September attacks provide a paradigm shift when it comes to protection of national security. It results in a trending vision that prioritized security over national security, which makes it essential to think about balancing national security with free expression as a pillar of democratization. This study focusses on how the balance between freedom of expression and national security interests is achieved. It studies the legal approached of the European court of human rights and its legal assessment to strike this balance. The findings of this analytical study asserts that in order for the ECtHR to achieve this balance, it implements the 3-part test indicated in the second paragraph of article 10, which include that the interference with free expression must be prescribed by law, pursued a legitimate aim and necessary for democratic society. The court examines each case to determine whether a restriction is legal or not up to those 3 requirements. Despite the fact that the court implement proportionality and margin of appreciation in its assessment of context and content, it is still remained unclear for legal thinkers, how the court logically determine the weight for each factor. This led to an open debate over the coherence and consistency. This study finds that the court’s discissions lack consistency and coherence, when it comes to the principle of proportionality and margin of appreciation implementation. This study believes that the ECtHR lacks the assessment of laws of the respondent state to determine whether they are compatible with the convention. Rather, it only assesses the implementation of those laws, namely the interference itself.